The validation of productivity on the changeover activity at the automotive stamping press line by comparing the embedded SMED frame-work versus SMED approach: A witness simulation case study - Basri, A.Q. (2019)
Single-Minute Exchange of Die (SMED) is a popular method used to optimize the die change processing time. The purpose of this study is to identify on how to reduce set-up time by using Embedded SMED in automotive stamping press line. An actual case study at an automotive company XYZ in Malaysia was conducted based on parts supply issues. The observations, assessments and standard manufacturing practices were carried out during the study. WITNESS simulation software was used to identify the critical processes and also enable the validation of actual output based on the production. The result of the particular press line (combination of 800 Tons and 500 Tons machines) which produced 6 parts in 1-shift operations with small lot size output has been identified and improved. The significant improvement based on the Embedded SMED compared to conventional SMED approach showed a decreasing change-over time from an average of 12.51 minutes to 9.41 minutes (effectively a single-digit minute) resulting in circa 62 reduction. Â© Published under licence by IOP Publishing Ltd.